2001
DOI: 10.1128/aac.45.1.170-175.2001
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of the New Ketolide Telithromycin (HMR 3647) Administered in Ascending Single and Multiple Doses

Abstract: Telithromycin (HMR 3647) is a novel ketolide antimicrobial with good activity against both common and atypical respiratory pathogens, including many resistant strains. This randomized, three-period crossover study determined the dose proportionality of telithromycin pharmacokinetics after single and multiple dosing in healthy subjects. In each treatment period, subjects received a single oral dose of 400, 800 or 1,600 mg of telithromycin followed 4 days later by the same dose once daily for 7 days. Blood and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
79
1
4

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(91 citation statements)
references
References 13 publications
7
79
1
4
Order By: Relevance
“…The slow release from the cells that was observed leads to prolonged retention of the substance in the body and probably influences the terminal half-life of the drug and, subsequently, the dosing regimen. The terminal half-lives after a single oral dose are about 40 h for azithromycin (7) and about 7 h for telithromycin (27), which thus allow once-daily dosing. On the other hand, clarithromycin and erythromycin, which have terminal half-lives of 4 h and 3 h, respectively (30), require multiple doses daily.…”
Section: Discussionmentioning
confidence: 99%
“…The slow release from the cells that was observed leads to prolonged retention of the substance in the body and probably influences the terminal half-life of the drug and, subsequently, the dosing regimen. The terminal half-lives after a single oral dose are about 40 h for azithromycin (7) and about 7 h for telithromycin (27), which thus allow once-daily dosing. On the other hand, clarithromycin and erythromycin, which have terminal half-lives of 4 h and 3 h, respectively (30), require multiple doses daily.…”
Section: Discussionmentioning
confidence: 99%
“…The lowest drug concentrations investigated (0.5 mg/liter for azithromycin, 0.06 mg/liter for telithromycin) correspond to the MICs (in broth) of the drugs for the strain of S. aureus used in this study; note that for azithromycin, the peak concentration observed for patients receiving a conventional dose (500 mg) did not exceed 0.4 mg/liter (24); for telithromycin, the highest concentration investigated (2 mg/liter) corresponds to the C max observed for patients after administration of a conventional dose (800 mg) (42). Each point corresponds to the mean value for three independent determinations.…”
Section: Fig 5 Variations In the Number Of Cfu Upon Incubation For mentioning
confidence: 99%
“…As a result, while the pharmacodynamic parameter most predictive of outcome (i.e., AUC/MIC) remains constant in the absence or the presence of neutrophils, the magnitude of drug exposure required to produce any given reduction in bacterial density is substantially reduced in the immunocompetent host. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]1998) evaluated the impacts of neutrophils on the bacteriostatic activity of telithromycin and a structurally related ketolide against S. pneumoniae strains with various macrolide susceptibilities in the murine thigh infection model and reported that the potencies of the ketolides are enhanced (1.8-to 24-fold) in the presence of neutrophils. Moreover, although neutropenic conditions were used in the present study, the enhanced in vivo potency of another ketolide, ABT-773, against pneumococci in immunocompetent hosts has also recently been demonstrated (5).…”
Section: Discussionmentioning
confidence: 99%
“…Mouse serum samples were analyzed by HPLC to quantitate the telithromycin concentrations (16). Serum samples to which an internal standard (moxifloxacin; Bayer Corp., West Haven, Conn.) was added were deproteinized by the addition of acetonitrile and centrifugation.…”
Section: Antimicrobial Test Agentsmentioning
confidence: 99%